Analysis of Landslide Vulnerability and Its Impact on Population and Infrastructure Exposure in Central Bogor District Using AHP and Open Geospatial Data - Vincent, Vincent; Ramadhanis, Zainab; Sutoyo, Sutoyo; Suharnoto, Yuli; Sudibyo, Tri (Departemen Teknik Sipil dan Lingkungan IPB, 2025)
Indonesia’s location at the convergence of three active tectonic plates makes it highly susceptible to various natural disasters, with landslides being among the most frequent and destructive, particularly in mountainous and densely populated urban areas. Central Bogor District in West Java represents a vulnerable area where steep topography, high rainfall intensity, and dense population heighten landslide risk. Despite recurrent landslide events, comprehensive vulnerability assessments integrating both physical and socio-environmental factors remain limited. This study aims to produce a spatially explicit landslide vulnerability map for Central Bogor District by utilizing open geospatial data and applying a GIS-based multi-criteria decision-making approach. The Analytical Hierarchy Process (AHP) was employed to assign weights to four primary physical parameters—rainfall, slope, lithology, and land cover—based on their relative contribution to landslide susceptibility. Supporting data were derived from Sentinel-1A imagery (InSAR), Landsat-8 classification, CHIRPS precipitation records, and official geological maps. These physical layers were then integrated with exposure indicators, including population density, infrastructure distribution, and accessibility data from OpenStreetMap. The results delineated three landslide vulnerability zones: high (49.87 ha), moderate (481.82 ha), and low (236.45 ha). High-risk zones, such as Gudang and Paledang Sub-districts, feature steep slopes, weak geological formations, and dense settlements. Overlay analysis also revealed a significant concentration of critical infrastructure within moderate-to-high vulnerability zones, highlighting exposure and potential service disruption during hazard events. The study underscores the critical value of combining open geospatial data with AHP-based weighting to inform targeted disaster mitigation, infrastructure planning, and resilient urban development. The resulting maps can guide policy and preparedness strategies to reduce landslide impacts in high-risk urban areas.